Effects of parietal injury on covert orienting of attention - Posner, MI (J Neurosci, 1984)
The cognitive act of shifting attention from one place in the visual field to another can be accomplished covertly without muscular changes. The act can be viewed in terms of three internal mental operations: disengagement of attention from its current focus, moving attention to the target, and engagement of the target. Our results show that damage to the parietal lobe produces a deficit in the disengage operation when the target is contralateral to the lesion. Effects may also be found on engagement with the target. The effects of brain injury on disengagement of attention seem to be unique to the parietal lobe and do not appear to occur with our frontal, midbrain, and temporal control series. These results confirm the close connection between parietal lobes and selective attention suggested by single cell recording. They indicate more specifically the role that parietal function has on attention and suggest one mechanism of the effects of parietal lesions reported in clinical neurology.